Are interim CEOs just caretakers? - He, Xiaoxiao; Zhu, Margaret Rui (Journal of Corporate Finance, 2020)
Interim CEOs are often viewed as caretakers during CEO transition periods. However, the caretaker function does not fully explain the increasing trend in the use of interim CEO appointments. Recent studies suggest that firms also use the interim position to test potential CEO candidates. This paper empirically examines this argument using a hand-collected dataset of 1936 CEO successions between 1994 and 2014. We find evidence that firms consider interim positions as a testing ground for CEO candidates. Specifically, we find that candidates with uncertain managerial abilities are more likely to be initially named as interim CEOs rather than permanent CEOs. We also find that interim CEOs are more likely to be promoted to the permanent CEO position when they have better interim-period performance attributable to managerial skills. Consistent with the testing-ground option hypothesis, we find interim CEOs promoted to the permanent position result in superior long-run performance, suggesting better CEO-firm matches.